Mongolia's Economic Diplomacy Policies : Domestic Challenges and Mongolian-China Opportunities - Wu, Jiayu; Druláková, Radka, 1973-; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
My thesis provides an in-depth look at how Mongolia has used economic diplomacy strategies to address its challenges as a resource-rich landlocked country, particularly in its relationship with China. Also, the thesis assesses how Mongolia's economic diplomacy strategy has helped the country identify opportunities for cooperation and development in a complex international political and economic environment. Which focuses on Mongolia's Belt and Road Initiative cooperation with China, analyzes the implications of this cooperation for Mongolia's domestic policy and international standing in addition to examining how this cooperation has aided in the development of Mongolia's infrastructure and economic growth. The article ends with several specific policy suggestions meant to improve Mongolia's economic and diplomatic approach to make more use of its advantages in terms of location and resources.
Vedoucí práce: Radka Druláková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses